Crack Propagation and Toughening Mechanism of Staggered Structure of Hydroxyapatite Sheets. Issue 1 (June 2020) - Liu, Yuxi; Li, Aihua; Lin, Xuedong
Abstract: Based on the macro-microscopic analysis of the fracture path of cortical bone, it is shown that the crack path of the cortical bone deflected obviously during bending fracture, which indicates that the microstructure of the cortical bone affects the crack propagation of the bone. According to the microstructure of cortical bone, a staggered structure analysis model of hydroxyapatite (HA) sheets was established, and the effects of the structural parameters and volume content of hydroxyapatite sheets on the crack deflection coefficient and fracture toughness were compared and analyzed. The analysis results show that the structural parameters and volume fraction of hydroxyapatite sheets are positively correlated with the fracture toughness of bone. When the bone is fractured, the cracks deflected between the staggered hydroxyapatite layers to dissipate more energy, thereby improving the fracture toughness of the bone. The research results can provide useful guidance for the design and manufacture of high-performance bionic bone composites.